2020
DOI: 10.1021/acs.langmuir.0c01307
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Interaction Mechanism between Benzohydroxamic Acid and Mineral Surface in the Presence of Pb2+ Ions by AFM Force Measurements and First-Principles Calculations

Abstract: Probing the interaction mechanism between organic molecules and material surfaces in the presence of metal ions is of great importance in many fields, such as mineral flotation. The collectability of benzohydroxamic acid (BHA) to a spodumene (LiAl­(SiO3)2) mineral surface during mineral flotation could be enhanced with the addition of metal ion activatorsPb2+ ions. Pb2+ ions could be added as either Pb–BHA complex formed by premixing Pb2+ ions and BHA molecules at a given ratio or sequential addition of Pb2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…17−25 The BHA can adsorb onto the cassiterite surface based on the chelation reaction of the hydroxamic acid group with the Pb 2+ site. 24,26,27 Recently, our work has proved that the adsorption of BHA has significantly changed the surface morphology of the cassiterite surface by the bridging lead ion. 28 Multivalent metal ions (i.e., Fe 3+ , Pb 2+ , Ca 2+ , and Bi 3+ ) were extensively investigated as activators in flotation.…”
Section: ■ Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…17−25 The BHA can adsorb onto the cassiterite surface based on the chelation reaction of the hydroxamic acid group with the Pb 2+ site. 24,26,27 Recently, our work has proved that the adsorption of BHA has significantly changed the surface morphology of the cassiterite surface by the bridging lead ion. 28 Multivalent metal ions (i.e., Fe 3+ , Pb 2+ , Ca 2+ , and Bi 3+ ) were extensively investigated as activators in flotation.…”
Section: ■ Introductionmentioning
confidence: 87%
“…The hydration process has altered surfaces of oxide minerals to be negative, which will produce a strong repulsive force between the anion collector and the surface. , Thus, metal ions are previously added and adsorbed on the mineral surface to provide positive sites. As shown in Figure , the hydrophilic cassiterite can be selectively separated from its gangues using benzohydroxamic acid (BHA) and lead ions as collector and activator, respectively. The BHA can adsorb onto the cassiterite surface based on the chelation reaction of the hydroxamic acid group with the Pb 2+ site. ,, Recently, our work has proved that the adsorption of BHA has significantly changed the surface morphology of the cassiterite surface by the bridging lead ion . Multivalent metal ions (i.e., Fe 3+ , Pb 2+ , Ca 2+ , and Bi 3+ ) were extensively investigated as activators in flotation. ,,, Lead ions have been reported to possess great selectivity to separate scheelite from a mixture of calcium-containing minerals. The flotation technology using metal ions as activators has achieved great successes in the past half century, but the underlying adsorption mechanism of reagents on mineral surface activated by metal ions has not been well revealed due to the complex multiphase solution chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, Hu et al utilized AFM force measurements to study the mechanistic aspects of the interaction between benzohydroxamic acid (BHA) and Pb-BHA complexes during the flotation of lithium pyroxene as well as the hydration behavior of Pb 2+ ions in flotation. Through AFM, they measured intermolecular forces and observed that the adhesion between the spodumene surface and BHA was stronger when Pb 2+ ions were mixed with BHA simultaneously, compared to sequential addition …”
Section: Introductionmentioning
confidence: 99%
“…The pre-assemble strategy is a newly proposed method to realize selective flotation via adding the mixture of collectors and the metal ions. It is found that the latter strategy shows very good flotation performance in the flotation of some important oxide minerals, that is, scheelite, cassiterite, rhodochrosite, and spodumene. ,,, Hu et al have investigated the interaction force difference between the two strategies with atomic force microscopy . It has been shown that BHA possesses a strong chelating ability with the free Pb 2+ in aqueous solution and Pb adsorbed by the oxide surface.…”
Section: Introductionmentioning
confidence: 99%
“…9,17,18,39−41 Hu et al have investigated the interaction force difference between the two strategies with atomic force microscopy. 40 It has been shown that BHA possesses a strong chelating ability with the free Pb 2+ in aqueous solution and Pb adsorbed by the oxide surface. However, the surface coordination mechanism has not been well-elucidated.…”
Section: ■ Introductionmentioning
confidence: 99%